A Case Report of Citelli's Abscess: A Rare Complication of Mastoid Abscess - Aroor, Rajeshwary; Sharma, Ayushi (Journal of Health and Allied Sciences NU, 2025)
Middle ear and the tympanic membrane are complex structures. Anatomy is destroyed in cases with extensive inflammation. It is better to avoid middle ear surgical intervention in such cases until the inflammation subsides. Here, we present a 70-year-old immunocompromised male, who presented with foul-smelling discharge from the right ear and a painful swelling over right side of the neck, diagnosed as a case of coalescent mastoiditis with abscess along the digastric muscle. Patient was successfully managed with initial incision and drainage of the abscesses and intravenous antibiotics without manipulating the middle ear and external auditory canal.
Keywords: mastoid abscess; surgery; middle ear surgery